Crystallization, spectral, crystallographical, and thermoanalytical studies of succinobucol polymorphism - Jurček, Ondřej; Lahtinen, Manu; Wimmer, Zdeněk; Drašar, Pavel; Kolehmainen, Erkki (Journal of pharmaceutical sciences, 2012)
Four different polymorphs, A, C, D, and E, of succinobucol were isolated and characterized by means of solid-state nuclear magnetic resonance spectroscopy, single crystal and powder X-ray diffraction, differential scanning calorimetry, thermogravimetry, and attenuated total reflection-infrared spectroscopy. From a number of experiments, the same polymorphs (C, D, and E) and an equilibrium phase mixture B consisting of polymorphs C and D were repeatedly gained using different solvents or their mixtures. Although polymorph A was obtained directly from recrystallization only on few occasions, polymorphs C, D, and E proved to be metastable kinetic polymorphs, which slowly transform to a thermodynamically more stable form A during long-term storage. The single-crystal structures of polymorph C and D were determined by X-ray single-crystal diffraction.
Keywords: krystalografie rentgenová; Spectrophotometry, Infrared; prášková difrakce; probukol; Powder Diffraction; Thermogravimetry; Calorimetry, Differential Scanning; Crystallization; Probucol; magnetická rezonanční spektroskopie; Crystallography, X-Ray; molekulární modely; krystalizace; diferenciální skenovací kalorimetrie; termogravimetrie; Models, Molecular; spektrofotometrie infračervená; Magnetic Resonance Spectroscopy